Panhuwas: A regional short film on sexual abuse, blind faith, and folk healing - Santiago, Ma. Isabelle Y. (Animo Repository, 2022)
This project is a regional short film, a visual allegory, on the abuse of cultural beliefs and traditions, the cultivation of false beliefs, and the potential for culture or known beliefs to be weaponized as means for personal gain. The short film specifically tackles sexual abuse committed through the indoctrination of cultural beliefs. Folk healing is a tradition of medicine in some provinces of the Philippines, and has been present in the culture even before the colonization period. The healing techniques use a variety of herbal therapies, treatments, and religious beliefs to cure illnesses caused by spirits. However, there have been reported cases of sexual abuse committed by folk healers in these communities, and brings up the issue of the cultivation of blind faith in culture and/or religion. Considering that folk healers are highly respected in these cultures and are considered as being chosen by a higher power, people who have been taught these ideas for their whole lives are susceptible to blind following. This project does not aim to condemn the religious cultural beliefs, but rather to study the susceptibility of blind faith in religion to abuse, and how the abuser uses religion as a means to justify sexual violence. The project aims to effectively portray the psychological effects of abuse, the methods of the abuser, and the culture of communities that practice folk healing.